HANDOUT OF PIDADA (Sonneratia) IN COASTAL MANGROVES AS ENRICHMENT OF BIODIVERSITY MATERIAL CONCEPTS - Murdiah Murdiah; Hardiansyah Hardiansyah; Mahrudin Mahrudin (ATRIUM PENDIDIKAN BIOLOGI, 2022)
Plant diversity is a local potential that can be developed into educational enrichment tool, especially biology, which is closely relate to all living things. One of the materials that discusses is diversity. Pidada (Sonneratia) is one of mangroves in the coastal area of Sungai Rasau, Tanah Laut Regency, which can be used as learning resource. Therefore, teaching materials were made in the form of handouts. This study aims to analyze validity of the handout. The development model used is Tessmer (1998), which is limited only to self-evaluation and expert review. The results data analysis showed that the handout developed was declared very valid as a whole by three validators, validity score 92.43%.